Деякі безпекові питання в концепції ранньохристиянської політико-правової думки Середньовіччя - Загуменна, Ю. О.; Zagumenna, Yu. O.; Юлія Загуменна (Supremaţia Dreptului = Верховенство Права: междунар. науч. журн. – 2017. – № 2. – С. 216-222, 2017)
Досліджено деякі безпекові питання в концепції ранньохристиянської філософсько-правової думки Середньовіччя, на прикладі комплексного аналізу фундаментальної праці Святого Августина «Про Град Божий».

The influence of the concept of “Civitas Dei” on security issues in the medieval political and legal thought has been revealed in the article. The purpose of the article is to study some security issues within the concept of early Christian philosophical and legal thought. Based on the example of a comprehensive analysis of the fundamental work of St. Augustine “Civitas Dei”, it has been determined that the security concept was grounded on the original creative synthesis of security ideas developed by the ancient political and legal tradition, on the one hand, and Christian doctrine, on the other hand, as well as it contained the deep political and legal analysis of security issues against the background of both the current problems of the Roman state of that time and the generalization of the historical experience of the formation and development of state-organized human societies throughout previous human history.
Keywords: Середньовіччя; безпека; публічна безпека; Святий Августин; «Про Град Божий»; політико-правова думка; Middle Ages; security; public safety; St. Augustine; «On the City of God»; political and legal opinion; Средневековье; безопасность; публичная безопасность; Святой Августин; «О Граде Божием»; политико-правовая мысль